2020
DOI: 10.3389/fphys.2020.579892
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle miRNAs in the Promotion of Cardiac Neovascularisation

Abstract: Cardiovascular disease (CVD) is the leading cause of mortality worldwide claiming almost 17. 9 million deaths annually. A primary cause is atherosclerosis within the coronary arteries, which restricts blood flow to the heart muscle resulting in myocardial infarction (MI) and cardiac cell death. Despite substantial progress in the management of coronary heart disease (CHD), there is still a significant number of patients developing chronic heart failure post-MI. Recent research has been focused on promoting neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 195 publications
(152 reference statements)
0
21
0
1
Order By: Relevance
“…MiRNA has been widely used in cancer and other diseases, and has been the center of attention in the field of CHD. [ 31 33 ] I has been proved that MiRNA-21 can promote cell proliferation and antagonize apoptosis, which affects the formation of neointima in vascular wall and participates in the pathological process of vascular stenosis. [ 34 ] The researches of miRNA-21 on ischemic heart disease is still in its infancy, and the role of restenosis after PCI is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA has been widely used in cancer and other diseases, and has been the center of attention in the field of CHD. [ 31 33 ] I has been proved that MiRNA-21 can promote cell proliferation and antagonize apoptosis, which affects the formation of neointima in vascular wall and participates in the pathological process of vascular stenosis. [ 34 ] The researches of miRNA-21 on ischemic heart disease is still in its infancy, and the role of restenosis after PCI is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cell therapy to rescue and restore cardiomyocytes, increasing research suggests that promoting the survival of cardiac endothelial cells, treating cardiac angiogenesis, and mediating the recanalization of cardiac collaterals have great therapeutic potential for the treatment of myocardial infarction. Examples include angiogenesis gene therapy (82), proangiogenic stem cell therapy (83), angiogenic ncRNA therapy (84), and exosome-and exosome-derived proangiogenic ncRNA therapy (85)(86)(87)(88). For example, a study by Ma et al showed that exosomes derived from murine BMSCs can deliver MIR132, induce tube formation in HUVECs in vitro, and promote angiogenesis in the ischemic area of the infarcted heart in mice (89).…”
Section: Cardiac Angiogenesismentioning
confidence: 99%
“…EVs lack immunogenicity; thus, they demonstrate potential as a cell-free drug for tissue regeneration in an animal model [ 15 ]. Furthermore, they have displayed therapeutic efficacy against ischemic heart disease [ 16 ] and kidney disease [ 17 ] and promoted wound healing [ 18 ] and cartilage regeneration [ 19 ]. However, the therapeutic efficacy of EVs in meniscus regeneration is uncertain.…”
Section: Introductionmentioning
confidence: 99%